2018
DOI: 10.3390/su10124776
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Modeling of Critical Success Factors for Enhancing Sustainability and Performance in E-Learning

Abstract: E-learning, a technology-mediated learning approach, is a pervasively adopted teaching/learning mode for transferring knowledge. Some of the motivational factors for its wide adoption are time and location independence, user-friendliness, on-demand service, resource richness, and multi-media and technology driven factors. Achieving sustainability and performance in its delivery is of paramount importance. This research utilizes the critical success factors (CSFs) approach to identify the sustainable E-learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 40 publications
(62 reference statements)
4
37
1
2
Order By: Relevance
“…Past studies have indicated that critical success factors (CSFs) play a vital role in the successful implementation of E-Learning. Furthermore, it has also been revealed that the critical factors of different dimensions can have varying effects on the E-Learning system [14][15][16]. Therefore, it is imperative to explicitly investigate the assessment and prioritisation of E-Learning's CSFs and propose a hierarchical model of E-Learning's success factors.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have indicated that critical success factors (CSFs) play a vital role in the successful implementation of E-Learning. Furthermore, it has also been revealed that the critical factors of different dimensions can have varying effects on the E-Learning system [14][15][16]. Therefore, it is imperative to explicitly investigate the assessment and prioritisation of E-Learning's CSFs and propose a hierarchical model of E-Learning's success factors.…”
Section: Introductionmentioning
confidence: 99%
“…The general challenges that are faced in the adoption of cloud computing remain the same irrespective of the sector. The literature review shows that there have been researches to determine the major factors and challenges in the success of cloud computing [10,[30][31][32][33][34]. These factors may be listed as cost-reduction, flexibility, virtualness, availability, collaboration, scalability, efficiency, redundancy and reliability, data management, service management, governance, product-process control and monitoring, infrastructure, system reliability, information and visualization security, data security and concerns over data transmission across anticipated broadband speeds.…”
Section: Csfs For Cloud Computing In Institutions and E-learningmentioning
confidence: 99%
“…Mobile learning implementation is a highly interdisciplinary area involving active participation from multiple domains. There are studies that tried to integrate the multiple domains in E-Learning [10], cloud-based E-Learning [11] and mobile learning [12]. Most studies have considered the constructs from the technical side and behavioral side.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To discuss our research question, the study is organized as follows: We first provide the essentials of the conceptual and theoretical background of our proposal by illustrating the link between knowledge sharing, social capital, and socio-cognitive perspective and a concise focus on the theoretical notion of the complex value of agrifood aggregations. Then, we present the methodological approach adopted, highlighting elements useful to the subsequent discussion where we analyze how knowledge sharing becomes a facilitator [34][35][36][37] in the co-creation of sustainable value when relative strategies are activated following certain policies and specific operational interventions. Finally, we provide the conclusions and we highlight the main managerial and research implications.…”
Section: Introductionmentioning
confidence: 99%